The theory behind corporate restructuring; The performance of UK reverse Leveraged buy-outs. - Crook, James Matthew (2007)
We compare the performance of UK reverse leveraged buy-outs to that of the AIM and FTSE 250 indexes during the period, 1990 - 2000. The mean performances of indexes and the equity sample are measured over two and four year periods, using the daily prices of the indexes and the market capitalisations of the equities. Significant differences in performance were not found to exist but the mean performance of indexes exceeded that of the reverse LBO sample with large effect sizes. Given the available literature the two main determinants of firm performance, level of managerial ownership and the level of debt leverage, are investigated and found to have insignificant effects. The proportion of variance that can be explained by the regression model is extremely small. We return to our literature and find the basis for our predictions to have been founded on US samples. Our results force us to conclude that the UK and US do not face the same principal-agent problem due to the differing nature of how the equities are held.